Evaluation of common and rare variants of Alzheimer's disease-causal genes in Parkinson's disease. (April 2022) - Zeng, Qian; Pan, Hongxu; Zhao, Yuwen; Wang, Yige; Xu, Qian; Tan, Jieqiong; Yan, Xinxiang; Li, Jinchen; Tang, Beisha; Guo, Jifeng
Abstract: Introduction: Parkinson's disease (PD) and Alzheimer's disease (AD) are the most common neurodegenerative diseases in the elderly. Recently, some variants of AD-causal genes ( APP, PSEN1, PSEN2 ) have been reported in PD. In this study, we investigated the association between coding variants of AD‐causal genes and PD in a large Chinese population cohort. Methods: We performed whole-exome sequencing (WES) on 1, 917 patients with early-onset or familial PD and 1, 652 controls, and whole-genome sequencing (WGS) on 1, 962 sporadic late-onset PD and 1, 279 controls. Genetic and phenotypic data were analyzed with regression analyses and the optimized sequence kernel association test. Further validation study was performed by Fisher's exact test. Results: We found that rs75733498 in the PSEN2 gene was significantly associated with early-onset or familial PD; however, no significant relationship was discovered between rs75733498 and sporadic late-onset PD. The result of the validation study still revealed a significant association between rs75733498 and PD. We observed a suggestive association with APP gene in early-onset or familial PD when considering damaging missense variants alone ( p  = 0.018) or combined with loss‐of‐function variants ( p  = 0.029). Further phenotypic analysis did not demonstrate any significant associations. Conclusion: Our results support a possible genetic contribution of AD-causal genes to PD. These findings warrant further genetic and functional confirmation, and more powerful association studies will better decipher the mechanisms of PD. Highlights: Two different NGS technologies were applied in early-onset or familial PD and sporadic late-onset PD separately. Rs75733498 in the PSEN2 gene was significantly associated with PD. A suggestive contribution of damaging missense variants in APP to early-onset or familial PD was detected.